PEMBERDAYAAN SENTRA PRODUK LOKAL DALAM MENINGKATKAN PEMBANGUNAN BANGSA - Widani, Ni Made (Jurnal MBE Manajemen Bisnis, Equilibrium, 2022)
Community participation in nation building has a very deep meaning, because a prosperous nation depends on the welfare of its people. A prosperous society is a situation where people are able to improve the quality of their independence in overcoming problems in life. Community development in development implies that humans are placed in the position of actors and beneficiaries of the process of finding solutions and achieving development outcomes. The formation and change of good behaviour in the dimensions of all aspects of human life which includes the range of welfare from material to non-material in the dimensions of short-term to long-term time. In terms of community empowerment through the development and utilization of local products, one of them is by taking part in the proud national movement to use Indonesian products so that growing and increasing love for domestic products is one of the efforts to build national independence, which contributes to supporting the development of the nation.